2012
DOI: 10.5897/ajb11.4208
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Tanzanian elite sweet potato genotypes for sweet potato virus disease (SPVD) resistance and high dry matter content using simple sequence repeat (SSR) markers

Abstract: A total of 57 sweet potato genotypes with high dry matter content and resistant to sweet potato virus disease (SPVD) were characterized using four simple sequence repeat (SSR) markers. The germplasm included 20 genotypes identified as having high dry matter content and 25 accessions tolerant to SPVD in a study conducted in Tanzania in 2008. The total number of alleles within the 57 genotypes across 4 loci was 395, with an average of 4 alleles per locus. The unweighted pair group method with arithmetic mean (UP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…This suggestion might be supported by Dominguaz [20] who reported that dry matter content is genetically controlled trait in sweet potato. Catherine and Scott [21,22] reported that the dry matter percentage of different sweet potato varieties were between 13.4 and 29.2%, 25.23 and 41.11%, respectively. Tsakama, Fred, Bonsi and Loretan [23][24][25][26] also found that the dry matter in storage roots were ranged from 12.5 to 30.2, 29 to 39.07, 25 to 42 and 25.5 to 31.7%, respectively.…”
Section: Marketable Unmarketable and Total Storage Root Numbermentioning
confidence: 99%
“…This suggestion might be supported by Dominguaz [20] who reported that dry matter content is genetically controlled trait in sweet potato. Catherine and Scott [21,22] reported that the dry matter percentage of different sweet potato varieties were between 13.4 and 29.2%, 25.23 and 41.11%, respectively. Tsakama, Fred, Bonsi and Loretan [23][24][25][26] also found that the dry matter in storage roots were ranged from 12.5 to 30.2, 29 to 39.07, 25 to 42 and 25.5 to 31.7%, respectively.…”
Section: Marketable Unmarketable and Total Storage Root Numbermentioning
confidence: 99%
“…Similarly, Gwandu et al (2012) analyzed 57 sweet potato genotypes in Tanzania with 4 SSRs and found alleles from 11 to 22.…”
Section: Genetic Variabilitymentioning
confidence: 99%
“…In that study, 255 alleles were identified at 21 loci with an observed heterozygosity of 0.71 across populations. Gwandu et al (2012) examined diversity within 57 Tanzanian elite sweetpotato genotypes using four SSR markers. The results showed no specific clustering based on disease, dry matter content, or geographic location.…”
Section: Introductionmentioning
confidence: 99%